The efficacy of vitamin C on postlaparoscopic shoulder pain: a double-blind randomized controlled trial - Moon, Sungho; Lim, Se Hun; Cho, Kwangrae; Kim, Myoung-hun; Lee, Wonjin; Cho, Yong Hyun (Anesthesia and pain medicine (Korean society of anesthesiologists), 2019)
Background: This study evaluated the effect of vitamin C on post-laparoscopic shoulder pain (PLSP) in patients undergoing benign gynecological surgery during the first 72 h. Methods: Sixty patients (aged 20 to 60 years, with American Society of Anesthesiologists physical status classification I or II) scheduled for elective laparoscopic hysterectomy were enrolled in this study. The vitamin C group (Group C) received 500 mg of vitamin C in 50 ml of isotonic saline infusion intravenously twice a day from the day of surgery to the third day after surgery. Patients in the saline group (Group S) received the same volume of isotonic saline over the same period. Post-operative analgesic consumption, pain scores of the incision site and the shoulder, and the incidence of PLSP were all evaluated at 1, 6, 24, 48, and 72 h following surgery. Results: Cumulative post-operative fentanyl consumption was significantly less in Group C at 24 and 48 h after surgery (P = 0.002, P = 0.012, respectively). The pain intensity of PLSP was also significantly lower in Group C 24 h after the operation (P = 0.002). Additionally, the incidence of PLSP was significantly lower in Group C 24 and 48 h after the operation (P = 0.002, P = 0.035, respectively). Conclusions: Perioperative intravenous administration of vitamin C (500 mg, twice a day) reduced post-operative analgesic consumption and significantly lowered the pain intensity and incidence of PLSP. KCI Citation Count: 0